Isolation and Phisicochemical Characterization of Microcristalline Cellulose from Ramie (Boehmeria nivea L. Gaud) Based on Pharmaceutical Grade Quality - Nawangsari, Desy; Yohana Chaerunisaa, Anis; Abdassah, Marline; Sriwidodo, Sriwidodo; Rusdiana, Taofik; Apriyanti, Linda (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Microcrystalline cellulose is the most used material for medicine, which able to be found in fibrous plants. Microcrystal celluloses are being used as filler or binder in dosage formulas in tablets and capsules. This research aimed to produce microcrystalline cellulose from ramie based on pharmaceutical grade parameters. Research method include hemp fiber preparation, Î±-cellulose isolation, microcrystalline cellulose production, and microcrystalline cellulose characterization which compare with AvicelÂ® PH 102 . Result shown microcrystalline cellulose yield is 57.26%. The result of physicochemical characterization that can comply the specifications of pharmaceutical grade as a pharmaceutical excipient.Â Keywods :Â Microcrystalline cellulose, Ramie, physicochemical, pharmaceutical grade.